Validitas E-Petunjuk Praktikum Berbasis Problem Based Learning Materi Pencemaran Lingkungan untuk Meningkatkan Kemampuan Berpikir Kritis - Muthohharoh, Siti; Nuraida, Dede (FKIP Unirow Tuban, 2024)
The aim of this research is to develop practical instructions based on problem based learning, on the topic of environmental pollution. This type of research is development research or Research and Development (R&D) with the ADDIE development model, namely analysis, design, development, implementation and evaluation. This research was only carried out until the development stage. The instrument to measure validation is in the form of a questionnaire which will be validated by the validator. The validation questionnaire is filled in by three validators. Validation results were analyzed using validity techniques. The results of the research show that the validity of practical instructions based on Problem Based Learning from the material aspect obtained an average score of 84.75% with a valid category, from the language aspect obtained an average score of 82.85% with a valid category, and from the graphic aspect obtained a score of 80. 32% with valid category. The overall validity score of the practical instructions developed was 82.64% in the valid category. Based on the results of this research, it can be concluded that the biology practicum guide based on problem based learning on environmental pollution material that was developed has met the validity criteria.